Assessment of sustainability of forest management practices on the operational level in northwestern Russia – a case study from the Republic of Karelia - Trishkin, Maxim; Lopatin, Eugene; Shmatkov, Nikolay; Karjalainen, Timo (Taylor & Francis, 2017)
The main aim of the article is to assess the consequences of newly proposed legislative initiative on introducing intensive forest management practices in Russia. Implementation of norms and its effect on sustainable forest management practices have been analysed in this study on one enterprise operating in the Republic of Karelia. This meant modelling of forest growth, clear cuts and regeneration within 100 km radius from the mill for two alternative management scenarios with fixed demand of wood based on current norms and decreasing harvesting age to half from the current. Wood demand of the enterprise, structure and accessibility of forest resources, i.e. forest road infrastructure were taken into account in the analysis. Both forest management scenarios decreased the total growing stock significantly, and therefore considered as non-sustainable practices. In addition, forest age structure was more uneven for both scenarios at the end of the simulation period. Comparison of two alternative management practices showed that the implementation of intensive forest management in Russia requires new norms that would be based on principles of sustainable forest management.
Keywords: annual allowable cut; clear-cut; Republic of Karelia; clear felling; sustainability